1977
DOI: 10.1007/bf01419913
|View full text |Cite
|
Sign up to set email alerts
|

An economical rural mental health consumer satisfaction evaluation

Abstract: An economical direct and indirect consumer satisfaction evaluation was conducted in a rural community mental health center. The inquiry consisted of determining whether clients felt better after a therapy session than prior to it and if they were satisfied with the clinic services. Adjective Generation Technique (AGT) scores indicated that consumers felt significantly better after a psychotherapy session than the comparison group. Results from a postcard survey seem to support this finding, suggesting that app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Moreover, in the published studies, where more careful reporting of return rates is likely, response rates are even lower. Of the studies of consumer satisfaction reviewed for this article, 31 indicated return rates; of these 10 report return rates between 21% and 40%, 8 between 41% and 60%, 7 between 61% and 80%, and 6 between 81% and 100% (Ahmed & Koltuv, 1976;Balch, Ireland, Mc-Williams, & Lewis, 1977;Birnbaum & Suits, 1979;Burgoyne, Wolken, Staples, Kline, & Powers, 1977;Ciarlo & Reihman, 1977;Denner & Halprin, 1974a, 1974bEdwards, Yarvis, Mueller, & Langsley, 1978;Fiester & Fort, 1978;Frank, 1974;Getz, Fujita, & Allen, 1975;Gilligan & Wilderman, 1977;Glenn, 1978;Goyne & Ladoux, 1973;Hart & Bassett, 1975;Heineman & Yudin, 1974;Jansen & Aldrich, 1973;Justice & McBee, 1978;Kissel, 1974;Kline, Adrian, & Spevak, 1974;Koltuv et al, 1978;Landsberg, 1975;Love et al, 1979;Mayer & Rosenblatt, 1974;Noll & Block, 1979;Powell et al, 1971;Preston, Schoenfeld, & Adams, 1975;Reinhart & Cazavelan, 1975;Slem & Cotler, 1973;Snelling & Walker, 1978;Strupp, Fox, & Lessler, 1969;Woodward et al, 1978). High rates of return are virtually limited to captive samples in which responses are likely to be highly reactive (typical phone and mail surveys average 41 % and 46% responding, respectively).…”
Section: Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in the published studies, where more careful reporting of return rates is likely, response rates are even lower. Of the studies of consumer satisfaction reviewed for this article, 31 indicated return rates; of these 10 report return rates between 21% and 40%, 8 between 41% and 60%, 7 between 61% and 80%, and 6 between 81% and 100% (Ahmed & Koltuv, 1976;Balch, Ireland, Mc-Williams, & Lewis, 1977;Birnbaum & Suits, 1979;Burgoyne, Wolken, Staples, Kline, & Powers, 1977;Ciarlo & Reihman, 1977;Denner & Halprin, 1974a, 1974bEdwards, Yarvis, Mueller, & Langsley, 1978;Fiester & Fort, 1978;Frank, 1974;Getz, Fujita, & Allen, 1975;Gilligan & Wilderman, 1977;Glenn, 1978;Goyne & Ladoux, 1973;Hart & Bassett, 1975;Heineman & Yudin, 1974;Jansen & Aldrich, 1973;Justice & McBee, 1978;Kissel, 1974;Kline, Adrian, & Spevak, 1974;Koltuv et al, 1978;Landsberg, 1975;Love et al, 1979;Mayer & Rosenblatt, 1974;Noll & Block, 1979;Powell et al, 1971;Preston, Schoenfeld, & Adams, 1975;Reinhart & Cazavelan, 1975;Slem & Cotler, 1973;Snelling & Walker, 1978;Strupp, Fox, & Lessler, 1969;Woodward et al, 1978). High rates of return are virtually limited to captive samples in which responses are likely to be highly reactive (typical phone and mail surveys average 41 % and 46% responding, respectively).…”
Section: Validitymentioning
confidence: 99%
“…Upon examination of the most general satisfaction item in each survey, the following results emerge. 3 Among the 26 studies that examine satisfaction in outpatient or in mixed community mental health center populations (which are principally outpatient) and that report summary statistics, 3 find satisfaction in 91%-100% of clients, 10 in 81%-90%, 8 in 71%-80%, 4 in 61%-70%, and 1 in 51%-60% (Balch et al, 1977;Birnbaum & Suits, 1979;Burgoyne et al, 1977;Ciarlo & Reihman, 1977;Denner & Halprin, 1974a, 1974bEdwards etal, 1978;Fiester, 1979;Frank etal., 1977;Gilligan & Wilderman, 1977;Goyne & Ladoux, 1973;Hart & Bassett, 1975;Heineman & Yudin, 1974;Justice & McBee, 1978;Kaufmann, Sorenson, & Raeburn, 1979;Kissel, 1974;Kline et al, 1974;Landsberg, 1973Landsberg, , 1975Love et al, 1979;McCoy, Penick, Powell, & Read, 1975;Noll & Block, 1979;Powell et al, 1971;Reinhart & Cazavelan, 1975;Strupp et al, 1969;Woodward et al, 1978). Among the inpatient studies, 2 show satisfaction in 81%-90% of clients, 2 in 71%-80%, and 2 in 61%-70% (Ahmed & Koltuv, 1976;Eder & Kukulski, 1975;Glenn, 1978;Landsberg, 1973;Mayer & Rosenblatt, 1974;Snelling & Walker, 1978).…”
Section: Level Of Reported Satisfactionmentioning
confidence: 99%
“…Its validity, reliability and usefulness as a tool in mental health program evaluation have been demonstrated elsewhere (Allen and Potkay, 1973;Gilligan and Wilderman, 1977). The method consists of having a subject generate five adjectives that best describe oneself or some other specified person.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Recent legislation requires the periodic evaluation of Federally funded community mental health centers. The community is also making consistent demands that social programs provide accountability (Gilligan & Wilderman, 1977). This review is therefore prepared at a time when the pressures for program evaluation appear to be stronger than ever.…”
mentioning
confidence: 99%